Chemical composition, anti-inflammatory activity and cytotoxicity of Thymus zygis L. subsp. sylvestris (Hoffmanns. & Link) Cout. essential oil and its main compounds - Rodrigues, Vanessa (2019)
Thymus L. is one of the most aromatic and medicinal plants used worldwide, mainly due to its essential oils. Several species of Thymus are currently used in herbal medicine for the prevention and treatment of various diseases, including disorders of the respiratory, gastrointestinal and nervous system. Moreover, they are widely used by their flavor as condiment and food preservatives, and a wide range of biological and therapeutic properties have been reported for this genus. The aim of the present research was to evaluate the anti-inflammatory activity of Thymus zygis L. subsp. sylvestris (Hoffmanns. & Link) Cout. oil and its major compounds and, of utmost importance, assess their safety profile in several mammalian cell types at concentrations presenting strong bioactivity.